Is platelet transfusion associated with hospital-acquired infections in critically ill patients?. Issue 1 (December 2017) - Aubron, Cécile; Flint, Andrew; Bailey, Michael; Pilcher, David; Cheng, Allen; Hegarty, Colin; Martinelli, Antony; Reade, Michael; Bellomo, Rinaldo; McQuilten, Zoe
Abstract Background Platelets are commonly transfused to critically ill patients. Reports suggest an association between platelet transfusion and infection. However, there is no large study to have determined whether platelet transfusion in critically ill patients is associated with hospital-acquired infection. Methods We conducted a multi-centre study using prospectively maintained databases of two large academic intensive care units (ICUs) in Australia. Characteristics of patients who received platelets in ICUs between 2008 and 2014 were compared to those of patients who did not receive platelets. Association between platelet administration and infection (bacteraemia and/or bacteriuria) was modelled using multiple logistic regression and Cox regression, with blood components as time-varying covariates. A propensity covariate adjustment was also performed to verify results. Results Of the 18, 965 patients included, 2250 (11.9%) received platelets in ICU with a median number of 1 platelet unit (IQR 1–3) administered. Patients who received platelets were more severely ill at ICU admission (mean Acute Physiology and Chronic Health Evaluation III score 65 (SD 29) vs 52 (SD 25), p < 0.01) and had more comorbidities (31% vs 19%, p < 0.01) than patients without platelet transfusion. Invasive mechanical ventilation (87% vs 57%, p < 0.01) and renal replacement therapy (20% vs 4%, p < 0.01) were more frequently administered in patients receiving platelets than in patients without platelets. On univariate analysis, platelet transfusion was associated with hospital-acquired infection in the ICU (7.7% vs 1.4%, p < 0.01). After adjusting for confounders, including other blood components administered, patient severity, centre, year, and diagnosis category, platelet transfusions were independently associated with infection (adjusted OR 2.56 95% CI 1.98–3.31, p < 0.001). This association was also found in survival analysis with blood components as time-varying covariates (adjusted HR 1.85, 95% CI 1.41–2.41, p < 0.001) and when only bacteraemia was considered (adjusted OR 3.30, 95% CI 2.30–4.74, p <0.001). Platelet transfusions remained associated with infection after propensity covariate adjustment. Conclusions After adjustment for confounders, including patient severity and other blood components, platelet transfusion was independently associated with ICU-acquired infection. Further research aiming to better understand this association and to prevent this complication is warranted.